The statistics of segmentation and classification - Leventhal, Barry (Henry Stewart Talks, 2008)
The process of building a segmentation, Define business objectives, Obtaining and preparing data, Stages of the segmentation process, Extract principal components or key variables, Method A: identify most discriminatory variables, Method B: use principal components analysis, A graphical explanation of principal components, Cluster analysis, A graphical view of cluster analysis, Interpreting clusters, Testing the segmentation, Segment migration analysis, Communicate and deploy the segmentation, Classifying individuals to segments, Classification of further individuals Apply existing segmentation model, Build segment attribution model, Survey segmentation attribution process, Summary of main points